The Influence of Price and Location on Student Decisions in School Selection (Case Study at SMA Mulia Buana Parung Panjang, Bogor Regency) - Ferdiansyah Ferdiansyah (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of price and location on student decisions in school selection (Case Study at SMA Mulia Buana-Parung Panjang, Bogor Regency) partially and simultaneously. This study uses quantitative associative research methods and the population that is used as the object of this research is the whole sample using the saturated sample technique, namely the students of class X SMA Mulia Buana totaling 52 students. The results of this study simultaneously have a significant positive effect between price and location on the decisions of SMA Mulia Buana students. The results of the correlation coefficient (R) of 0.738 which means that there is a strong correlation or relationship between price, and location has a strong relationship to student decisions. The coefficient of determination is 54.5%, so price and location can contribute 54.5% to student decisions while the rest is influenced by other factors. The multiple linear regression equation Y= 3.986 + 0.596 X1 + 0.290 X2. And the results of the Hypothesis Test (F test) of 25.925 > 3.19 and significant 0.000 < 0.05, then Ho is rejected and Ha is accepted which means that the price (X1) and location (X2) simultaneously have a significant effect on the decisions of high school students (Y) Mulia Buana Parung Panjang-Bogor.